The 77 years (1941-2018) evolution of mastika’s cover: a visual framing of the Malay audience’s interests - Mohamed, Shafizan; Zulkarnain, Hanis Safiyyah; Mamat, Najmi Syahiran (Global Academic Excellence (GAE), 2019)
This article analyses how Mastika magazine, one of the oldest and most established lifestyle magazines in Malaysia, framed the Malay interest throughout its 77 years of publication. The study applies framing theory and design principles to examine how the magazine presented the interests of its Malay audiences through the designs of its covers. A visual analysis of 80 covers from 1941 to 2018 was performed, comparing several aspects concerning both the content of the magazine and the art design. Results showed that the evolution of Mastika can be explained through 6 time phases that captured a dynamic use of images and graphics to define and represent the interest of the Malay audiences.